Implantación de un sistema contable y aplicación de indicadores financieros en Automotriz Sobre Ruedas De La Ciudad De Piñas, provincia de el Oro, en el periodo noviembre-diciembre 2015 - Romero Añazco, Lisbeth Fabiola (2016)
The thesis entitled "IMPLATATION OF AN ACCOUNTING SYSTEM AND APPLICATION OF FINANCIAL INDICATORS IN THE AUTOMOTIVE SOBRE RUEDAS OF PIÑAS CITY PROVINCE OF EL ORO. IN THE PERIOD NOVEMBER – DECEMBER 2015" was developed under the system of permanent account, in order to provide the owner of self-propelled wheeled quality information that would contribute to improving the economic situation - current financial business, for making the correct decisions. To develop the investigation was considered to be the stated objectives and proceeded to the preparation of the accounting records and auxiliary devices needed for the proper registration of their operations; moreover, considering the economic activity and the activities developed by the automotive was also adapted a plan and manual of accounts. Continued with the preparation of the initial inventory of all goods, rights and obligations that owns the automotive, continuing with the accounting records in the logbook proceeded to make the book more and to develop the trial balance of sums and balances, later with the help of the worksheet, the Financial Statements were prepared. Finally using the information provided in the Financial Statements applies the most relevant financial indicators of liquidity, indebtedness, activity and profitability with their respective interpretations that allow us to know the performance of automotive in the period developed. According to the results obtained, it was concluded that the lack of an accounting system on the self-propelled wheeled does not allow one to determine with accuracy the economic situation - financial, so it is recommended to the owner of the business to continue applying this system of accounting, since it will allow you to organize and control their resources effectively and obtain better results.